DEVELOPING A SELF-CONFIDENCE SNAKES-AND-LADDERS BOARD GAME FOR JUNIOR HIGH SCHOOL COUNSELING SERVICES - Eko Saputro; Ade Irma Novianti; Dewi Masyitoh (CV. TOTUS TUUS, 2026)
Low self-confidence among junior high school students is frequently associated with passive classroom participation, hesitation to express opinions, and difficulty coping with academic and social challenges, indicating a need for engaging guidance and counseling media. This study aimed to develop an educational board game, “Self-Confidence Snakes and Ladders,” as a counseling medium to strengthen students’ self-confidence. The study employed a Research and Development (R&D) approach adapted from a modified Borg & Gall model through four stages: needs analysis, product design, expert validation, and limited field testing. Participants consisted of a content expert, a media expert, a prospective user (guidance and counseling teacher), and a small group of junior high school students. Data were collected using feasibility assessment sheets based on a 4-point Likert scale covering accuracy, usefulness, feasibility, attractiveness, suitability, and ease of use, and were analyzed descriptively. The results showed high feasibility across reviewers: the content expert rated the product 3.33, the media expert 3.40, the prospective user 3.37, and the small-group trial 3.50, all within the “very good” category, with minor suggestions related to refining question wording, improving font clarity, and adjusting session duration. In conclusion, the developed game is highly feasible and well-received as a practical counseling medium that can promote interactive and enjoyable student engagement. Future studies should evaluate effectiveness using experimental designs, larger samples, and validated self-confidence outcome measures.